Measuring trust in nurses – Psychometric properties of the Trust in Nurses Scale in four countries - Stolt, Minna; Charalambous, Andreas; Radwin, Laurel E.; Adam, Christina; Katajisto, Jouko K.; Lemonidou, Chryssoula; Patiraki, Elisabeth; Sjövall, Katarina; Suhonen, Riitta A. (My University, 2016)
Purpose The purpose of this study was to examine psychometric properties of three translated versions of the Trust in Nurses Scale (TNS) and cancer patients’ perceptions of trust in nurses in a sample of cancer patients from four European countries. Methods A cross-sectional, cross-cultural, multi-site survey design was used. The data were collected with the Trust in Nurses Scale from patients with different types of malignancies in 17 units within five clinical sites (n = 599) between 09/2012 and 06/2014. Data were analyzed using descriptive and inferential statistics, multivariate methods and psychometrics using exploratory factor analysis, Cronbach's alpha coefficients, item analysis and Rasch analysis. Results The psychometric properties of the data were consistent in all countries. Within the exploratory factor analysis the principal component analysis supported the one component structure (unidimensionality) of the TNS. The internal consistency reliability was acceptable. The Rasch analysis supported the unidimensionality of the TNS cross-culturally. All items of the TNS demonstrated acceptable goodness-of-fit to the Rasch model. Cancer patients trusted nurses to a great extent although between-country differences were found. Conclusions The Trust in Nurses Scale proved to be a valid and reliable tool for measuring patients’ trust in nurses in oncological settings in international contexts.
Keywords: Cancer care; Cross-cultural study; Nurse; Nursing; Psychometrics; Rasch analysis; Scale; Trust